Consumer Protection and the Uniform Commercial Code - Jean Braucher (Washington University Law Quarterly, 1997)
The Symposium's authors include participants in the drafting process, some of whom defend it and its products and some of whom are more critical, as well as nonparticipants who can view the consumer proposals with more detachment. Most of the authors, as well as the law review's editors, have had to struggle with the task of evaluating moving targets, as draft upon draft in each project produced changes large and small.
Keywords: Commercial law; Consumer protection